Correlation between asymmetrical hip rotation in individuals with and without osteoarthritis of knee: a cross sectional study - DR. ANAND HEGGANNAVAR; LINATA WALAVALKAR; DR. SANTOSH METGUD (International Journal of Pharma and Bio Sciences, 2018)
Osteoarthritis is the degenerative condition of the joints that affects the cartilage and the surrounding structures. It is one of the most common ailments that is affecting human joints worldwide. According to the studies done on asymmetrical hip rotation, weakness of hip abductors and external rotators are the main impairments in patellofemoral pain, whereas asymmetry in hip rotation could be caused due to its relationship to hip rotator strength and the position of the muscle during the test. The determinants of functional impairments in osteoarthritis knee are quadriceps strength, knee pain and age. There is a direct relation between knee pain, asymmetry of hip and muscle weakness. There is paucity in literature on asymmetrical hip rotation and knee osteoarthritis which can be a cause for osteoarthritis of knee. Therefore, the present study aims to determine the correlation between asymmetrical hip rotation in patients with knee osteoarthritis and comparing with normal age matched individuals.56 subjects of mean age 52.00±6.63 were included in the present study. Group A included all subjects with mild or moderate knee osteoarthritis as per Le Quesne’s questionnaire and group B included all age matched individuals. Asymmetrical hip rotation and muscle strength was noted.There was a significant difference in asymmetrical hip rotation in both the groups (0.0001) Asymmetrical hip rotation was high in group A. The strength of the internal and external rotators was more in the subjects in group B. But there was no correlation found between knee osteoarthritis and asymmetrical hip rotation (p=0.785).Asymmetrical hip rotation was more in subjects with knee osteoarthritis than in age matched individuals. There was no correlation found between knee osteoarthritis and asymmetrical hip rotation.